Microecological aspects of relationship between skin microbiota and psoriasis - Arsenyeva A.A.; Lyamin A.V.; Migacheva N.B.; Orlov E.V.; Alekseev D.V. (Клиническая микробиология и антимикробная химиотерапия)
Over the last years, influence of the human microbiome on the emergence of non-infectious chronic diseases including psoriasis has become a popular research field. A significant goal is to get an answer to the following question: are changes in the skin microbiota a cause or consequence of inflammatory process in psoriasis? This review provides an integrated approach to the problem and study of relationships between changes in microbiological landscape and microecological features of the skin. During the analysis of scientific literature, such aspects were studied as the living conditions of skin microorganisms, the participation of microbiota in maintaining microecological homeostasis of the skin, impairments of the skin microbiota functions during psoriasis. In particular, various patterns of deviations in the composition of microbiological communities are considered, such as an increase in the ratio of individual pathogens (Staphylococcus aureus and Streptococcus pyogenes) and a decrease in the number of microorganisms that limit the growth of pathogenic flora (Staphylococcus epidermidis and Cutibacterium acnes). This review also focuses on certain contradictions in various studies of the skin microbiota in psoriasis, which are most likely to be caused by variable methodological approaches. It is crucial to develop ways of studying human skin microbiota structure, particularly at the strain level, in order to define microbiological predictors of remission and exacerbations, as well as to evaluate treatment efficacy.